Reconstruction of technology for frame videoinformation flow telecommunication network - Бараннік, Володимир Вікторович; Кривонос, Володимир Миколайович (Ukrainian Information Security Research Journal, 2013)
It is shown that with intensive growth and the use of modern information technologies, the need in enhancing the effectiveness of existing systems transmission and storage of video data. Substantiates the necessity using new techniques with the preliminary compression of video information based on the transformation by orthogonal transformations. Set forth rationale that the provision of timely and reliable information possible on die basis of die development of mutually-univocal video data renewal processes. Developed the technology for reconstruction component transforms, based on die reconstruction of the low-frequency components of the transformants, a significant component of the vector by obtaining positional numbers with unequal adjacent components and vector scaling based component decoding Bodo. Sets out the sequence, and basic recovery steps describe of each constituent the vector transformants. It is shown that the proposed method allows the for reconstructionto restore transformants without introducing errors, provide the necessary credibility.